Los afiches como recurso metodológico para mejorar el aprendizaje sobre la diversidad de la fauna en las islas galápagos, con los estudiantes del noveno grado de educación general básica paralelo B del centro de formación artesanal Monseñor Francisco Valdivieso Alvarado de la ciudad de Loja, periodo 2014-2015 - Valladarez Calva, Danny Daniel (2016)
Today's education requires teachers to use methodological resources to motivate students so that it improves the teaching - learning. Among the resources used for this purpose are the posters, the same as when using a variety of images, colors and text, become a valuable teaching aid for improving learning. This research work has the purpose of applying the posters as a methodological resource to enhance learning about the diversity of wildlife in the Galapagos Islands. In this context, for this investigation the following issue was raised: TO CHECK HOW DOES THE APLICATION OF THE POSTERS INFLUENCE AS METHODO LOGIC OPTION TO STRENGTHEN THE LEARNING ABOUT DIVERSITY OF THE FAUNA IN THE GALÁPAGOS ISLANDS, WITH THE STUDENTS OF THE NINTH GRADE OF GENERAL BASIC EDUCATION PARALLEL "B" OF THE CRAFT FORMATION CENTER "MONSEÑOR FRANCISCO VALDIVIESO ALVARADO" OF THE LOJA CITY, ACADEMIC PERIOD 2014-2015. The general objective was raised: To apply the posters as methodologic option to strengthen the learning about diversity of the fauna in the Galápagos Islands, with the students of ninthn grade of General Basic Education parallel “B” of the Craft Formation Formation Center "Monseñor Francisco Valdivieso Alvarado" of the Loja city, academic period 2014-2015. The used methods were: analytic, to analyze the obtained information; the synthetic one, to synthesize the obtained information of the situation of the object to investigate; the inductive one, to determine the theoretical referents of the investigation; and, the deductive one that was used to determine the conclusions and recommendations. As technical the survey, the bibliographical technique and the correlation of Pearson were used; the instruments, the questionnaire, the bibliographical record and the pre test-pos test. The population corresponds 47 students, of where she took a sample of 20, that you/they conform the ninth parallel grade "B”. With the analysis, discussion and interpretation of the obtained data you evidences that the students have scarce knowledge on the topic; also that the educational one to the moment to impart their classes carries out it in a traditional way, in a theoretical way and with not very motivational resources for the learning; what allowed the application of the posters in the thematic one, after that which the technique of correlation of Pearson was applied that threw positive results, of that which is deduced that the application of posters like methodological resource, were able to improve the learning in the students about the diversity of the fauna in the Galápagos Islands.